PD-1/PD-L1 Inhibitors in Cervical Cancer - Liu, Yuncong; Wu, Li; Tong, Ruizhan; Yang, Feiyue; Yin, Limei; Li, Mengqian; You, Liting; Xue, Jianxin; Lu, You (Frontiers in Pharmacology, 2019)
As one of the most common gynecological tumors, a majority of cervical cancer patients in the early stage can recover well through surgical treatment and concurrent chemoradiotherapy (CCRT). However, for patients with recurrent, persistent, metastatic cervical cancer, effective treatment is rare, aside from bevacizumab combined with chemotherapy. To this end, programmed cell death-1/programmed cell death-ligand 1 (PD-1/PD-L1) inhibitors might be a novel choice for improving the clinical outcomes of these patients. Thus far, some pivotal trials, including Keynote 028, Keynote 158 and Checkmate 358, have indicated some clinical benefit of PD-1/PD-L1 inhibitors in cervical cancer. In light of these data, the FDA has approved pembrolizumab for patients with recurrent or metastatic cervical cancer with disease progression during or after chemotherapy. There are also some ongoing studies that may provide more evidence for the PD-1/PD-L1 pathway as a therapeutic target. In this review, we have summarized the status and application of PD-1/PD-L1 inhibitors in clinical trials for the treatment of cervical cancer and suggested some future directions in this field.